Preventing Cyberbullying with Islamic Values: Reviewing the Role of Islamic Religious Education Teachers in Shaping the Digital Ethics and Morals of the Young Generation - Mi'razfauzi, Wildan Ahmad (Multidiscience : Journal of Multidisciplinary Science, 2025)
The increasing prevalence of cyberbullying among students demands a preventive approach that goes beyond technical solutions, incorporating moral and religious values. This study aims to analyze the strategic role of Islamic Religious Education (IRE) teachers in preventing cyberbullying by internalizing Islamic values within students’ digital ethics. Using a descriptive qualitative approach through a literature review, this research examines academic literature, educational policy documents, and previous studies to construct a thematic understanding of the IRE teachers’ contributions in shaping students’ character in the digital era. The findings reveal that IRE teachers hold significant potential as moral agents in instilling Islamic digital ethics, such as honesty, mutual respect, and the prohibition of harming others. Cyberbullying prevention efforts can be more effective when supported by Islamic-based digital literacy training, contextual pedagogical strategies, and collaboration among schools, families, and religious institutions. This study contributes to the development of a curriculum that is responsive to digital challenges and provides a foundation for educational policies focused on fostering digitally literate youth with strong moral character rooted in Islamic values.